STUDI PEMETAAN DAERAH GENANGAN BANJIR DAS SEI KAMBING DENGAN SISTEM INFORMASI GEOGRAFIS - Zevri, Asril (Teras Jurnal : Jurnal Teknik Sipil, 2019)
Sei Sikambing River Basin is one of the Sub Das of Deli River which has an important role in water requirement in Medan City. Rainfall with high intensity is supported by changes in land use causing floods which reach 0.6 m to 1 m from river banks. The purpose of this study was to map the Sei Kambing River basin flood inundation area as information to the public in disaster mitigation efforts. The scope of this research is to analyze the maximum daily rainfall with a return period of 2 to 100 years, analyze flood discharge with a return period of 2 to 100, analyze flood water levels with HECRAS software, and spatially map flood inundation areas with GIS. The results showed that the return flood rate of the Sikambing watershed with a 25-year return period of 211.94 m3/s caused the flood level of the Sikambing watershed to be between 1.7 m to 3.7 m. The Sikambing watershed flood inundation area reached an area of 1.19 Km2 which resulted in the impact of flooding on 5 sub-districts in Medan, namely Medan Selayang District, Medan Sunggal, Medan Petisah, Medan Helvetia, and West Medan.